Keadilan sahabat: Konsep, kontroversi, dan kritik dalam tinjauan ahlus sunnah wal jamaah - Mas Muhammad Bahri (STAI Syaichona Moh. Cholil Bangkalan, 2016)
Actually justice companions (al-friend) is a classic discourse. Embryo had already existed in the end of the fourth Caliph, Ali ibn Abi Talib. Post-event arbritase controversial Muslims totally insulated in a veil of ideology and political interests. Each group has its own perspective of looking at the phenomenon, and each of them claimed his party who has the right to monopolize the truth. No exception justice in discourse companions. Sunnis, which is a representation of the sound of the authorities and the majority of the people expressed tawaqquf in this matter. The whole good friends were fluttering al-friends and shighar al-companions considered are equal and equally status as narrator fair. Even some people to extreme acts by lifting the notch companions at a level impossible to sin (Ma'shum). On the contrary, birth is also another extreme attitude that is radically assume that the majority of companions had lapsed. Dominated the fanatical followers of Ali (the Shia Ali) is successfully expanding its influence, to the subsequent development of their own design ideas of its own in the history of the transmission paths friends 'enemies' Ali. It is this attitude that arise to the massive resistance movement (great refusal) to all forms of transmission that comes apart from the path of Ahlul Bait and friend of Ali.